Equity Valuation in Amman Bourse - Tawfiq H. Abdel-Jalil; Ali Thuniebat (Journal of Accounting, Business and Management (JABM), 2009)
This paper aims to improve our understanding to the changes in stock prices in Amman Bourse, by examining the determinants of three valuation multiples: price to sales (PS), price to book value of equity (PBVE), and price to earnings (PE) ratios. A widely practiced technique for a firm's equity valuation is to use the stock price multiple to a historical accounting performance measure. Price is divided by net sales (NS), book value of equity (BVE), and earnings per share ( ). Net profit margin (NPM) is a measure of the sales' effect on stock price. The evolution of (PBVE) ratio is mainly measured by return on equity (ROE). Dividends payout ratio (DPR) is an important measure of (PE) ratio. In addition, these multiples facilitate the analysis, and the comparison between companies in the same industry. Consistent with the economic theory this paper found that: 1. Price to sales ratio is significantly positively related to net profit margin. 2. Price to book-value of equity ratio is significantly negatively related to return on equity ratio. 3. Price to earnings ratio is significantly positively related to dividends payout ratio. In other words, stock price changes in proportion to changes in net profit margin, and dividend payout ratios. Future research can take into account the effect of systematic risk on the valuation multiples.